Management Information Systems Towards Improving the Quality of Nursing Care Services: A Literature Review - Neli Suharti; Tutik Sri Hariyati (UIMA Press, 2024)
Background: Many developing countries are striving to further develop health information technology at the healthcare service level, particularly through the implementation of electronic health records (EHR). Objectives: This research aims to evaluate the quality and impact of implementing electronic health records in healthcare services from various perspectives. Methods: The research design employed in this study is a literature review, involving the collection of articles from selected databases, including PubMed and Cochrane. The article search started from the year 2014, and the Boolean operators used were